Development of Single-station Early Warning Lightning Alarm System - Wan Ismail, Ibrahim; Mohd Riduwan, Ghazali; Suliana, Ab Ghani; Mohd Falfazli, Mat Jusof (2013)
Lightning is one of the spectacular natural phenomena which happen on the earth. More than 2000 people are killed worldwide by lightning each year. The lightning monitoring system is important as the early warning alarm system. In this paper,lightning warning alarm system which can monitor and observe the lightning activity has been discussed. The system able to trigger the warning alarm whenever a lightning strikes at a particular area in 10 km radius from UMP Pekan, Pahang, Malaysia. The LabVIEW software was used as a data logger to measure, analyze and calculate the lightning distance. The accuracy of the system has been compared and validated by the Pekan Lightning Detection System (PLDS).